The perceptions of physical therapists about facilitators and challenges in the use of different tools for resistance training in COPD patients: a mixed-method study - Ana Paula Coelho Figueira Freire; Juliana Souza Uzeloto; Bruna Spolador de Alencar Silva; Marcia Rodrigues Costa Franco; Dionei Ramos; Ercy Mara Cipulo Ramos (Universidade de São Paulo, 2019)
ABSTRACT This study sought to quantify and qualitatively analyze the perception of physical therapists about facilitators and the challenges in the use of different types of tools for resistance training in chronic obstructive pulmonary disease (COPD) patients. This was a mixed-model study with qualitative analysis developed in a rehabilitation center. Six physical therapists who performed a randomized clinical trial were interviewed. The protocol consisted of the evaluation of three types of resistance training: elastic tubes, elastic bands, and training with conventional weight machines. After completion of the randomized trial, therapists were invited to participate in a focus group to collect qualitative data. Physical therapists also answered a quantitative questionnaire containing closed questions. The main outcome measures were the opinion of physical therapists about the advantages and disadvantages in clinical practice of each of the analyzed tools. The focus group analysis resulted in eight themes: Insecurities regarding load and handling tools, implementation of home-based treatment, improvements of tools, advantages and disadvantages of tools, incidence of injuries with elastic tools, patient's preferences, and particularities of the tools. Physical therapists pointed out different challenges and facilitators for resistance training. Characteristics of the tools such as costs, portability, handling and practicality were cited as factors that influence clinical practice. In the quantitative analysis, no differences were observed when comparing the scores of each instrument. The three tools analyzed are applicable and feasible in the clinical practice of physical therapists; moreover, they present different characteristics and particularities that should be considered, such as cost, clinical applicability, portability and perception of the patient and therapists.